Inflammatory potential of cotton‐based surgically invasive devices: Implications for cardiac surgery. Issue 6 (22nd November 2018) - Trunk, Stefan; Müllerbader, Pia; Hennig, Ulrike; Abel, Martin; Koggel, Annette; Stang, Katharina; Altreuter, Yvonne; Steger, Volker; Schlensak, Christian; Wendel, Hans P.; Stoppelkamp, Sandra
Abstract: Cotton‐based surgical invasive devices with their desired hemostyptic properties have been used for decades in the surgical field. However, in cardiac surgery using the heart–lung machine with direct retransfusion of suction blood, activated blood may re‐enter the circulation without filtration and may trigger a cascade reaction leading to systemic inflammation and thrombosis. We therefore set out to evaluate the inflammatory potential of untreated and pyrogen‐impregnated cotton‐based surgical invasive medical devices. After incubation of the swabs with whole blood or PBMC, the cell‐free supernatant was investigated for IL1β and IL6. While the reaction of human whole blood toward cotton swabs could not be influenced by any sterilization technique, dry heat and gamma‐irradiation were able to diminish the inflammatory reaction of PBMC toward the material and the used pyrogens. In conclusion, using PBMC in direct contact to cotton we are the first to establish a suitable test method for quantification of the pyrogenic/inflammatory activity of this material. The unaltered reaction of whole blood, however, suggests a crosstalk of cells and plasma proteins in the inflammation activation that is not prevented by sterilization of the swabs. This new in vitro testing methodology may help to better display the clinical situation during development of new materials. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1877–1888, 2019.